Mediation and judicial process: The problem of confidentiality - Arqueros Naranjo, Oscar Pablo (Revista de Estudios de la Justicia, 2022)
The main purpose of this text is to demonstrate that our Law 19.968, which creates the Family Courts, specifically its Title V relative to Family Mediation, is not satisfactorily elaborated, that is to say, it uses ambiguous and unclear language and in extreme cases does not regulate certain problems. This is the opposite of what happens in Spain, where mediation is regulated in specific laws, and its formulation is more detailed, solving problems that our law does not do. A clear example of this is the principle of confidentiality, the main subject of this article. In this regard, a hypothetical case will be used in which two parties in conflict request a family judge to declare admissible in the preparatory hearing, an expert report presented in a previous mediation that deals with the psychosocial or socioeconomic needs of the child. Can the judge declare that evidence admissible? Or, on the contrary, should he declare it inadmissible for being contrary to the principle of confidentiality established in article 105 letter C of Law 19,968? Does our law say something about that issue? Which principle has greater value, the principle of confidentiality or others such as the best interests of the child? Ideally, our legal system would regulate all events that occur in reality, however, this is not feasible, therefore, it is the duty of judges and lawyers to always seek the best solution for the conflict that unfolds before them even when the law does not determine a specific solution, being there fundamental the general principles of law that nourish our system, thus avoiding unfair decisions which may permanently affect family relationships.